A study on the sexual practices among selected young adults of Baranggay 3, Jaro, Leyte. - Acosta, Felice Sybil A.; Ranze, Doanne Jill T. (Felice Sybil A. Acosta, 2009)
The Study on the Sexual Practices Among Selected Young Adults of Barangay 3, Jaro, Leyte is aimed on finding out the actual sexual experiences, both practices and beliefs, among selected twenty randomly selected young adults aged 18-22 of Barangay 3, Jaro, Leyte who were identified through purposive sampling. Moreover, it is also intended to gather possible reasons of why they engage in such activities or practices; to identify the significant differences of the sexual behaviors among the male and female respondents and also to confer about some moral aspects regarding human sexuality. Further, an open-ended set of guide questions were utilized by the researchers for all interviews done.